Voice lessons : classroom activities to teach diction, detail, imagery, syntax, and tone - Dean, Nancy, 1945- (Gainesville, FL : Maupin House, 2000)
Contains one hundred historically and culturally diverse passages from world literature that demonstrate how voice inflection and control influence the passage's meaning.
Includes index.
Professional
Keywords: English language -- Composition and exercises -- Study and teaching (Secondary); English language -- Composition and exercises -- Study and teaching